UNIT 20.13 Thermodynamic Analysis of Weak Protein Interactions Using Sedimentation Equilibrium. (1st August 2014) - Sergeev, Yuri V.; Dolinska, Monika B.; Wingfield, Paul T.
Abstract: Proteins self‐associate to form dimers and tetramers. Purified proteins are used to study the thermodynamics of protein interactions using the analytical ultracentrifuge. In this approach, monomer‐dimer equilibrium constants are directly measured at various temperatures. Data analysis is used to derive thermodynamic parameters, such as Gibbs free energy, enthalpy, and entropy, which can predict which major forces are involved in protein association. Curr. Protoc. Protein Sci . 77:20.13.1‐20.13.15. © 2014 by John Wiley & Sons, Inc.